2017
DOI: 10.1039/c6nr09610g
|View full text |Cite
|
Sign up to set email alerts
|

3D-printable, highly conductive hybrid composites employing chemically-reinforced, complex dimensional fillers and thermoplastic triblock copolymers

Abstract: The use of 3-dimensional (3D) printable conductive materials has gained significant attention for various applications because of their ability to form unconventional geometrical architectures that cannot be realized with traditional 2-dimensional printing techniques. To resolve the major requisites in printed electrodes for practical applications (including high conductivity, 3D printability, excellent adhesion, and low-temperature processability), we have designed a chemically-reinforced multi-dimensional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Using a similar strategy, the electrodes based on carbon nanotubes were also printed using a composite ink composed of silver nanoparticles and silver flakes and a thermoplastic polystyrene–polyisoprene–polystyrene (SIS) triblock copolymers. [ 164 ] The thermoplastic polymer was used to enhance shear thinning behavior. The high conductivity of the printed electrodes was easily obtained after post‐treatment at a temperature as low as 80 °C, without additional processing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar strategy, the electrodes based on carbon nanotubes were also printed using a composite ink composed of silver nanoparticles and silver flakes and a thermoplastic polystyrene–polyisoprene–polystyrene (SIS) triblock copolymers. [ 164 ] The thermoplastic polymer was used to enhance shear thinning behavior. The high conductivity of the printed electrodes was easily obtained after post‐treatment at a temperature as low as 80 °C, without additional processing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…The use of dynamic bonds which undergo reversible breaking, exchange and reformation could be utilized to modify the printability of polymers as well as imparting various advanced functions. [ 41–58,62–67,59,68,60,69,70,72,61,73,71,82,86–88,74–81,83–85,89–133,244,258 , …”
Section: Summary and Perspectivementioning
confidence: 99%
“…The isoprene segment with a glass transition temperature below À60 C can be partially melted even at room temperature, which contributes critically to the formation of the suitably adhesive printed structures. 14 As another characteristic of electrodes printed from composite pastes, they are sustainable in a polar solvent medium, as the SIS tri-block copolymer is soluble only in noncoordinating solvents. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 This can be accomplished if using 3D-printable, extremely foldable, highly conductive electrodes. Recently, we have reported a facile way of formulating 3D-printable, conductive composite paste comprising of silver akes and multi-walled carbon nanotubes decorated with aqueous silver nanoparticles, with a usage of simple dispensing technique; 14 but, an applicability toward 3D-printed origami electronics has not been suggested with a demonstration of foldable electrodes on paper substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent research has shown the feasibility of applying three-dimensional conductive patterns on electronic applications, such as sensors, electrodes, and wireless devices. [17][18][19] However, it is difficult to achieve both miniaturization and true three-dimensional metallic features. Moreover, rendering the substrate exibility is attracting much research interests.…”
Section: Introductionmentioning
confidence: 99%